Effect of α-ketoacid on the nutrition related indicators for chronic kidney disease - ZHU Hui; ZOU Yong (Linchuang shenzangbing zazhi)
Objective To study the curative effectiveness of α-ketoacid in the treatment of chronic kidney disease and its effect on the nutrition related indicators. Methods There were 100 patients with chronic kidney disease treated in our hospital from November 2015 to November 2017.According to different treatment methods,these patients were divided into experimental group( n =52) and control group( n =48). In the control group and experimental group,the patients were treated with traditional treatment and low protein diet,and those in the experimental group were given α-ketoacid additionally. The treatment effects were observed and compared. Results Before the treatment,there was no significant difference in blood pressure and the level of inflammatory factors ( TNF-α,IL-6 and CRP) between two groups( P > 0.05),and after treatment,the levels of blood pressure and inflammatory related indicators in the experimental group were significantly lower than those in the control group( P < 0.05); Before the treatment,there was no significant difference in renal function( eGFR,SCr,BUN and PRO) between two group( P > 0.05). Compared to the control group,the renal function in the experimental group was significantly improved after treatment( P < 0.05); In the experimental group,the ratio of treatment efficiency was significantly higher than that that in the control group( 82.69% vs. 62.50%,P < 0.05); Before the treatment,there was no significant difference in the nutrition related indicators between two groups( P > 0.05). There was significant difference in the nutrition related indicators between two groups( P < 0.05). Conclusions In the treatment of chronic kidney disease,α-ketoacid can improve the nutrition effectively.